Mechanistic investigation of domain specific unfolding of human serum albumin and the effect of sucrose. (18th September 2013) - Yadav, Rajeev; Sen, Pratik
Abstract This study is devoted to understand the unfolding mechanism of a multidomain protein, human serum albumin (HSA), in absence and presence of the sucrose by steady‐state and time‐resolved fluorescence spectroscopy with domain specific marker molecules and is further being substantiated by molecular dynamics (MD) simulation. In water, the domain III of HSA found to unfold first followed by domains I and II as the concentration of GnHCl is increased in the medium. The sequential unfolding behavior of different domains of HSA remains same in presence of sucrose; however, a higher GnHCl concentration is required for unfolding, suggesting stabilizing effect of sucrose on HSA. Domain I is found to be most stabilized by sucrose. The stabilization of domain II is somewhat similar to domain I, but the effect of sucrose on domain III is found to be very small. MD simulation also predicted a similar behavior of sucrose on HSA. The stabilizing effect of sucrose is explained in terms of the entrapment of water molecules in between HSA surface and sucrose layer as well as direct interaction between HSA and sucrose.